Hot zones of all traffic crashes in Hong Kong (1995-2021) [Interactive dashboard] - Ting Lian (9069725) (2025)
The interactive dashboard displays hot zones of crashes in Hong Kong from 1995 to 2021. The hot zones are identified using the methodology developed by Professor Becky P.Y. Loo's research team. This dashboard provides detailed information of the attributes and statistics of crash hot zones.